Фрагмент скіфського мідного казана з Поросся - Романюк, В.В. (Інститут археології НАН України, 2008)
Публікація ніжки мідного казана орієнтовно датованого V ст. до н. е., знайденого на поселенні біля с. Володимирівка Таращанського р-ну Київської обл. На поселении V в. до н. э. у с. Владимировка Таращанского р-на Киевской обл. были обнаружены обломки скифского котла, изготовленного из металлургически чистой меди. Сохранившийся фрагмент (ножка и часть дна) дает представление о технике изготовления котла, бывшего продукцией скифских либо местных лесостепных мастеров. The fragments of Scythian cauldron made of metallurgically pure copper were discovered at the 5th c. settlement near Volodymyrivka village of Tarashcha Region in Kyiv Oblast. The fragment preserved, a stem and a part of a bottom, gives an idea of metalwork technique used in making the cauldron, which was a production of Scythian or the local Woodedt-Steppe zone craftsmen.